Reversible Crumpling of 2D Titanium Carbide (MXene) Nanocoatings for Stretchable Electromagnetic Shielding and Wearable Wireless Communication. (9th December 2019) - Li, Yang; Tian, Xi; Gao, Si‐Ping; Jing, Lin; Li, Kerui; Yang, Haitao; Fu, Fanfan; Lee, Jim Yang; Guo, Yong‐Xin; Ho, John S.; Chen, Po‐Yen
Abstract: In the emerging Internet of Things, stretchable antennas can facilitate wireless communication between wearable and mobile electronic devices around the body. The proliferation of wireless devices transmitting near the human body also raises interference and safety concerns that demand stretchable materials capable of shielding electromagnetic interference (EMI). Here, an ultrastretchable conductor is fabricated by depositing a crumple‐textured coating composed of 2D Ti3 C2 T x nanosheets (MXene) and single‐walled carbon nanotubes (SWNTs) onto latex, which can be fashioned into high‐performance wearable antennas and EMI shields. The resulting MXene‐SWNT (S‐MXene)/latex devices are able to sustain up to an 800% areal strain and exhibit strain‐insensitive resistance profiles during a 500‐cycle fatigue test. A single layer of stretchable S‐MXene conductors demonstrate a strain‐invariant EMI shielding performance of ≈30 dB up to 800% areal strain, and the shielding performance is further improved to ≈47 and ≈52 dB by stacking 5 and 10 layers of S‐MXene conductors, respectively. Additionally, a stretchable S‐MXene dipole antenna is fabricated, which can be uniaxially stretched to 150% with unaffected reflected power <0.1%. By integrating S‐MXene EMI shields with stretchable S‐MXene antennas, a wearable wireless system is finally demonstrated that provides mechanically stable wireless transmission while attenuating EM absorption by the human body. Abstract : 2D titanium carbide–based ultrastretchable conductors are fabricated by harnessing the surface instability of pre‐stretched latex, showing strain‐invariant performance in stretchable electromagnetic interference (EMI) shields and wearable wireless communicators, respectively. Finally, a wearable antenna with on‐site EM protection for the human body is demonstrated, which exhibits mechanically stable and efficient wireless communication and shielding performance.